Tauhid dalam Tafsir Ibnu Katsir: Kajian Al-Fatihah 5 dan Al-Baqarah 21-22 untuk Akhlak - Hibatullaila Nur Sukma (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the concept of Tawhid contained in the Qur'an, specifically in Surah Al-Fatihah, verse 5, and Surah Al-Baqarah, verses 21-22, as well as its impact on moral education (akhlak) towards Allah. This research uses the library research method with a qualitative approach. Library research is a type of research that relies on literature sources such as books, journals, tafsir, and other relevant documents without involving data collection in the field. The qualitative approach is chosen because this research focuses on an in-depth study of the meanings and content of the text, particularly the values of Tawhid in the Qur'anic verses through tafsir analysis. This approach allows the researcher to systematically and objectively explore conceptual and interpretative data. The author refers to the book Al-Qur’an Al-Adziim by Imam Ibn Kathir to identify two main concepts of Tawhid: Tawhid Rububiyyah and Tawhid Uluhiyyah. Surah Al-Fatihah, verse 5, and Surah Al-Baqarah, verse 21, contain the concept of Tawhid Uluhiyyah, which is the oneness of Allah in worship, while Surah Al-Baqarah, verse 22, contains Tawhid Rububiyyah, which is the recognition of Allah as the Creator and Controller of the universe. The results of this study show that understanding this concept of Tawhid has a significant impact on moral education towards Allah. A correct understanding of Tawhid can enhance piety, sincerity, patience, gratitude, as well as reliance on Allah. Furthermore, this concept also encourages Muslims to constantly repent, remember Allah, and have a positive view of Him. Therefore, the application of the concept of Tawhid in daily life becomes an essential foundation in forming noble character in accordance with Islamic teachings. This study is expected to contribute to the development of moral education in the context of Islam.